Collaborative action of surface chemistry and topography in the regulation of mesenchymal and epithelial markers and the shape of cancer cells - Li, Junsheng; Lu, Hao; Grunze, Michael; Sleeman, Jonathan P.; Levkin, Pavel (ACS applied materials & interfaces, 2016)
Malignant transformation is associated with enhancement of cell plasticity, which allows cancer cells to survive under different conditions by adapting to their microenvironment during growth and metastatic spread. Much effort has been devoted to understanding the molecular mechanisms of these processes. Although the importance of the extracellular matrix and of surface properties in these mechanisms is evident, the direct impact of distinct physical and chemical surfaces characteristics on cell fate remains unclear. Here, we have addressed this question using HT1080 fibrosarcoma cells as a model. To examine the relationship between surface topography, chemistry, and cell behavior, hydrophobic poly(butyl methacrylate-co-ethylene dimethacrylate) (BMA-EDMA) and hydrophilic poly(2-hydroxyethyl methacrylate-co-ethylene dimethacrylate) (HEMA-EDMA) surfaces with three different topographies (microporous, nanoporous, and nonporous) were generated. These surfaces were then modified by photoinitiated grafting of three different methacrylate monomers to create surface chemistry gradients of either negatively (AMPS) or positively (META) charged or zwitterionic (MDSA) functionalities. Our results show that AMPS promotes cell spreading, but that META abolishes cell growth. META and MDSA grafted on microporous BMA-EDMA produced superhydrophilic surfaces with high globularity and elasticity, which modified the cell phenotype by inhibiting cell spreading, followed by loss of mesenchymal characteristics and a reduction in protein levels of the mesenchymal markers N-cadherin, beta-catenin, p120 catenin, and also of the adaptor proteins vinculin and paxillin that are associated with adhesion and cancer cell invasion. The effect was strengthened along the gradient, suggesting that the density of the functional groups plays a role in this process. On the nanoporous surface, only MDSA grafting resulted in a significant increase in cell number, a reduction in N-cadherin expression, increased beta-catenin and p120 catenin levels, as well as the appearance of the epithelial marker E-cadherin. This indicates that the cancer cells have a high plasticity that is triggered by the collaborative effect of physical and chemical surface properties.
Gesehen am 10.07.2019